A novel ultrasensitive peroxynitrite-specific fluorescent probe and its bioimaging applications in living systems. (February 2021) - Zeng, Xiaodan; Li, Zilu; Fu, Jing; Jiang, Cheng; Ma, Mingshuo; Zhu, Lin; Jin, Xing
Abstract: Peroxynitrite, one of the well-known reactive nitrogen species (RNS), which is considered to be an important oxidant. Besides, peroxynitrite plays an important role in the broad spectrum of biological processes, and it is also a vital participant in the emergence of cancer. To this end, the fluorescent probe PN-1 was rationally synthesized, which contains a coumarin-fused coumarin dye and borates as the specific recognition group. Probe PN-1 exhibits several obvious performances, for instance, high specificity, excellent sensitivity, and it could promptly respond toward ONOO − . Using this simple fluorescent probe, we achieved the imaging of endogenous and exogenous ONOO − fluctuations in living cells and zebrafish. Moreover, PN-1 has efficiently differentiated cancerous cells from normal cells owing to image their different native ONOO − levels, these results indicated that PN-1 is expected to be an analytical tool, for researching ONOO − related cancer biology and studying the related effect of ONOO − in food. Graphical abstract: Image 1 Highlights: The probe could quantitatively and sensitively detect ONOO − (DL = 4 nM). The probe possessed an ultrafast response for ONOO − (within 5 s). The probe displayed prominent selectivity towards ONOO − . The probe could track endogenous and exogenous ONOO − fluctuations in living cells and zebrafish. The probe could efficiently differentiate cancerous cells from normal cells.